The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-12179-4
|View full text |Cite
|
Sign up to set email alerts
|

RT-qPCR-based tests for SARS-CoV-2 detection in pooled saliva samples for massive population screening to monitor epidemics

Abstract: Swab, RT-qPCR tests remain the gold standard of diagnostics of SARS-CoV-2 infections. These tests are costly and have limited throughput. We developed a 3-gene, seminested RT-qPCR test with SYBR green-based detection designed to be oversensitive rather than overspecific for high-throughput diagnostics of populations. This two-tier approach depends on decentralized self-collection of saliva samples, pooling, 1st-tier testing with highly sensitive screening test and subsequent 2nd-tier testing of individual samp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, despite the resource-saving benefits 14 , 15 , 18 , 22 , clinical laboratories have been hesitant to implement pooled sample testing 23 due to: (1) stringent workflows which do not fit within existing laboratory operations, (2) a lack of clear guidance on how to implement such methods and (3) the perception that clinical sensitivity of the assay will be lost with pooling. The methods we propose in the current study are straightforward extensions of a simple SARS-CoV-2 testing method and can be easily conducted manually, without requiring additional investment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the resource-saving benefits 14 , 15 , 18 , 22 , clinical laboratories have been hesitant to implement pooled sample testing 23 due to: (1) stringent workflows which do not fit within existing laboratory operations, (2) a lack of clear guidance on how to implement such methods and (3) the perception that clinical sensitivity of the assay will be lost with pooling. The methods we propose in the current study are straightforward extensions of a simple SARS-CoV-2 testing method and can be easily conducted manually, without requiring additional investment.…”
Section: Discussionmentioning
confidence: 99%
“…Large pooled testing programs have successfully demonstrated the efficacy of pooled saliva testing for helping to keep schools safely open 15 , 29 , with pooled samples having a similar sensitivity to the molecular testing of individual samples, in terms of both qualitative and quantitative (comparable Ct values between pooled and individual samples) measures. It is important to note however, that during times of high virus prevalence, when a greater number of tests are expected to return a positive result, pooled testing strategies must be frequently reviewed and when necessary, updated to minimize the number of reflex tests required which can negate the resource-savings benefits of pooled testing 13 , 19 , 22 , 27 .…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need to implement rapid and specific techniques to efficiently detect SARS-CoV-2. Molecular tests such as reverse transcription-polymerase chain reaction (RT-PCR) and its quantitative variant RT-qPCR are excellent diagnostic options, given their ability to detect target nucleic acids with high sensitivity [ 2 ] ( Figure S1 ).…”
Section: Introductionmentioning
confidence: 99%
“…One advantage of these tests, as opposed to RT-PCR with fluorogenic probes, is that they allow for assessment of the amplification specificity by simply examining the amplicon melting curves at the end of the PCR [ 28 ]. While most SYBR Green-based RT-PCR assays have been established for naso or oropharyngeal specimens [ 16 , 18–27 ], a handful of studies showed promising evidence for using saliva samples in these tests [ 17 , 29–31 ]. However, all the protocols described thus far require prior viral RNA isolation, which increases the costs and time needed for testing.…”
Section: Introductionmentioning
confidence: 99%